TEACHING ACADEMIC ENGLISH TO PHD STUDENTS IN RUSSIA: А POSSE AD ESSE - Natalia G. Popova; Lyudmila B. Kuznetsova (Высшее образование в России, 2016)
Foreign language competencies are essential for a modern researcher. Teaching academic English to PhD students in Russia currently faces significant challenges of an institutional, methodological, methodical and organizational nature. The paper summarizes the results of the discussion held within the round table "English Speaking Environment" by English language teachers and higher education specialists at the 15th seminar-conference of the 5-100 Project in February 2016. Among the topical issues are: the absence of clearly formulated teaching aims and objectives, lack of suitably tailored syllabi and teaching materials, serious gaps in teacher training and inadequate foreign language competence of PhD applicants. Some recommendations for the optimization of this process are presented.